Artificial Intelligence to Support Human Learning in Improving Outcomes in Digital Era: Technological Literacy for Learning - Antono Damayanto; Nofirman Nofirman; Khasanah Khasanah; Endang Fatmawati; Ali Zaenal Abidin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper discussed the efforts of artificial intelligence to support learning towards improving high-quality outcomes through proving the results of field studies. The author believes that learning in the era of modern technology is appropriate for educators, especially teachers, to better adapt to technological developments, especially in the field of Artificial Intelligence, so that learning can be carried out with the help of technology. For this reason, the author has searched for data on this discussion from relevant and valid literature sources to answer hypotheses and problems. We have thoroughly reviewed this study with secondary data considering that this study is to gain an understanding that requires scientific evidence from previous studies. So that the data we have collected can be summarized as valid study answers, we try to examine it first. We carry out a phenomenological approach to get answers from several existing data that we analyze, code, and understand to get valid data findings. As a qualitative study, we also design the results of this study as a qualitative descriptive report with previous literature reviews, especially in the field of Artificial Intelligence and learning with human learning in the era of all computers. So based on our goal, we conclude that artificial intelligence technology is a learning method that helps achieve maximum and effective results. We admit that this technology cannot assess the role of teachers because technology does help humans achieve optimal learning outcomes by the results of the technology that was designed. Hopefully, these results are helpful in many learning contexts.